GFR ≤25 years postdonation in living kidney donors with (vs. without) a first‐degree relative with ESRD. Issue 3 (1st December 2017) - Matas, Arthur J.; Vock, David M.; Ibrahim, Hassan N.
Abstract : An increased risk of ESRD has been reported for living kidney donors, and appears to be higher for those donating to a relative. The reasons for this are not clear. One possibility is that ESRD is due to the nephrectomy‐related reduction in GFR, followed by an age‐related decline that may be more rapid in related donors. Between 1/1/1990 and 12/31/2014, we did 2002 living donor nephrectomies. We compared long‐term postdonation eGFR trajectory for donors with (n = 1245) vs. without (n = 757) a first‐degree relative with ESRD. Linear mixed‐effects models were used to model the longitudinal trajectory of eGFR. With all other variables held constant, we noted a steady average increase in eGFR until donors reached age 70: 1.12 (95% CI: 0.92‐1.32) mL/min/1.73m ² /yr between 6 weeks and 5 years postdonation; 0.24 (0.00‐0.49) mL/min/1.73m ² /yr between 5 and 10 years; and 0.07 (−0.10 to +0.25) mL/min/1.73m ² /yr between 10 and 20 years for donors with attained age less than 70. After age 70, eGFR declined. After we adjusted for predonation factors, the difference in eGFR slopes between related and unrelated donors was 0.20 mL/min/1.753 m 2 /year (0.07‐0.33). Our data suggests that postdonation, kidney donor eGFR increases each year for a number of years and that eGFR trajectory does not explain any increase in ESRD after donation. Abstract : Long‐term follow‐up of kidney donor renal function suggests that eGFR continues to rise for many years postdonation, and although there is a difference in slope between related and unrelated donors, for both groups, postdonation eGFR trajectory does not explain an increase in end‐stage renal disease after donation.